A deep analysis on future web technologies and protocols over broadband GEO satellite networks‡. (7th July 2015) - Caviglione, Luca; Celandroni, Nedo; Collina, Matteo; Cruickshank, Haitham; Fairhurst, Gorry; Ferro, Erina; Gotta, Alberto; Luglio, Michele; Roseti, Cesare; Abdel Salam, Ahmed; Secchi, Raffaello; Sun, Zhili; et al.
Summary The goal of this work was to understand the direction of the emerging web technologies and to evaluate their expected impact on satellite networking. Different aspects have been analysed using both real satellite testbeds and emulation platforms in different test sites in Europe. This analysis included an evaluation of those HTTP/2.0 specifications, which were implemented and released as open‐source code in the experimental release of the SPDY protocol. SPDY performance was evaluated over satellite testbeds in order to understand the expected interaction with performance‐enhancing proxies (including scenarios with a SPDY proxy at a satellite gateway), the impact of security and the effect of satellite capacity allocation mechanisms. The analysis also considered the impact of application protocols and the delay induced by end‐system networks, such as a satellite‐connected WiFi network. Copyright © 2015 John Wiley & Sons, Ltd.